1973
DOI: 10.1083/jcb.57.3.773
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON HISTONE FRACTION F2A1 IN MACRO- AND MICRONUCLEI OF TETRAHYMENA PYRIFORMIS

Abstract: Histone fraction F2A1 has been isolated and purified from macronuclei of the ciliate Tetrahymena pyriformis . It migrates as a single species on sodium dodecyl sulphate-acrylamide gel electrophoresis, with a molecular weight indistinguishable from that of calf thymus F2A1 . The solubility properties of Tetrahymena F2AI are also similar to those of calf thymus F2A1 . Electrophoretic analyses on urea-acrylamide gels indicate that Tetrahymena F2A1 consists of four or five subspecies, the two fastest having electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
1

Year Published

1975
1975
1996
1996

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…In previous studies we have shown that the antibody recognizes its antigen in nucleosomes (30) and in whole chromatin by in situ immunofluorescence (37). We have already shown that hyperacetylated forms of H4 histone can be found in macronuclei of vegetatively growing cells (37) of T. Thermophila and this is in agreement with electrophoretic analyses where the patterns of histones extracted from macro-and micronuclei are compared (21). This paper gives details of acetylation processes during the development of the new macro-and micronuclei in conjugating Tetrahymena thermophila.…”
supporting
confidence: 73%
“…In previous studies we have shown that the antibody recognizes its antigen in nucleosomes (30) and in whole chromatin by in situ immunofluorescence (37). We have already shown that hyperacetylated forms of H4 histone can be found in macronuclei of vegetatively growing cells (37) of T. Thermophila and this is in agreement with electrophoretic analyses where the patterns of histones extracted from macro-and micronuclei are compared (21). This paper gives details of acetylation processes during the development of the new macro-and micronuclei in conjugating Tetrahymena thermophila.…”
supporting
confidence: 73%
“…Most of the positive experimental indications for the postulated correlation are indirect in the sense that increased histone acetylation was observed concomitant with enhanced transcriptional activity (24)(25)(26)(27)(28)(29). It has also been shown, that susceptibility of chromatin to DNase I, which preferentially digests transcriptionally active chromatin (30), is associated with chromatin regions enriched with highly acetylated histones (31)(32)(33)).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were isolated as described (27,28). Chromatin was isolated by a modification of the method of Panyim et al (29).…”
mentioning
confidence: 99%
“…Thus, the relationship between the rate of cell replication and the extent of phosphorylation of histone F1 observed in a variety of other cell types (11)(12)(13)(14)(15)(16) MATERIALS AND METHODS Cell Culture. Tetrahymena pyriformis, strains WH-6 (Syngen 1, mating type I; a micronucleate strain) and GL (an amicronucleate strain), were cultured as described (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation